Berichte und Vortäge. - Deutsche Akademie der Landwirtschaftswissenschaften zu Berlin (Berlin., 1953)
Vol. 1- comprise reports of the academy's 1st- Festsitzung und wissenschaftliche Tagung.
V.1 originally issued without series title and numbering.
Mode of access: Internet.